Gastrointestinal parasitic nematodes in pet red-footed tortoises (Chelonoidis carbonaria) from Grenada, West Indies. Issue 6 (June 2020) - Coomansingh Springer, Camille; Kinsella, Mike; Vasuki, Vishakha; Sharma, Ravindra Nath
Abstract: This study identifies the endoparasites in Red-footed tortoises ( Chelonoidis carbonaria ) during March 2018 to March 2019 from Grenada, West Indies. Fecal samples from a total of 103 tortoises were collected and examined by simple fecal floatation techniques for parasitic eggs and oocysts. Adult parasites found in the feces were examined under the microscope for identification based on their morphology. Fecal samples for this research were collected from four parishes; St. Andrew, St George, St. John and St. Patrick. The overall prevalence of intestinal parasites among tortoises was 14.6%. The internal parasites consisted of nematodes belonging to three genera: Atractis, Labiduris and Proatractis . The most prevalent nematodes were Atractis spp. (86.7%), which included two species: A. thapari (7.7%) and A. marquezi (15.4%) followed by Labiduris gulosa (20%) and Proatractis parvicapiticaronata (13.3%). All nematodes of three genera found in red-footed tortoises in Grenada are reported for the first time. They are not zoonotic but are serious pathogens for tortoises. Abstract : Microbiology; Zoology; Veterinary medicine; Animal behavior; Gastrointestinal system; Red-footed tortoise; Gastrointestinal parasites; Nematodes; Grenada.